Lateral sediment erosion with and without the non-dense root-mat forming seagrass Enhalus acoroides. (31st May 2021) - Twomey, Alice J.; Saunders, Megan I.; Callaghan, David P.; Bouma, Tjeerd J.; Han, Qiuying; O'Brien, Katherine R.
Abstract: Coastal areas are at increasing risk from flooding and erosion due to coastal development and climate change. Seagrass meadows, like other coastal ecosystems, can stabilise sediments, indirectly reducing coastal erosion. There is evidence that seagrass can reduce both the erosion of seabeds and lateral erosion of seagrass cliffs. However, these previous studies have only considered seagrass species whose below-ground biomass form dense root mats. This study aimed to investigate whether Enhalus acoroides, a species which does not form root mats, reduces lateral erosion rates of seagrass cliffs. To do this, samples of E. acoroides collected in sandy sediments within Xincun Bay China were transplanted into a wave flume. Lateral erosion rates were measured under exposure to waves for five cliff heights over 1 h. There was an interaction between cliff height and time on the rate of erosion, with higher erosion rates earlier in the experiment for larger cliff heights. The cores with the E. acoroides persisted longer than unvegetated cores, regardless of cliff height, but this result was not assessed statistically due to constraints in the analyses. The below-ground biomass of E. acoroides samples in this study was higher than values previously reported in the literature. Overall, these results suggest that non-dense root-mat forming seagrass species may not provide equivalent sediment stabilisation as dense root-mat-forming species, likely due to the reduced binding structure of the roots in species such as Enhalus . Graphical abstract: Image 1 Highlights: Erosion rates of submerged Enhalus acoroides cliffs increased with cliff height. Presence of the seagrass Enhalus acoroides did not affect rates of erosion. Unlike all seagrass species used in previous measurements of erosion, Enhalus acoroides does not form dense root mats. There is a significant interaction between cliff height and exposure time on the volume of sediment lost from the cores. The effect of sediment grain size on rates of erosion within seagrass cliffs is unknown.